PENERAPAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 (PENYALAHGUNAAN NARKOTIKA DIKALANGAN PELAJAR) - Ahmad Arif; Rumainur Rumainur (INTELIGENSIA MEDIA, 2022)
Narcotics abuse against children or students is a criminal act or is in a very dangerous category so that handling in law enforcement must be more careful and thorough so that preventive efforts and prosecutions are effective. Law and enforcement against narcotics crime in Indonesia according to the law number 35 of 2009 concerning narcotics, how top protect children the misuse of drugs seen from the social aspect and the positive legal functioning of the state brings very good effects for the protection of the threat of development and growth of the nation’s generation. Narcotics are not pests that are harmful to the human body but are capable of killing human civilization together. So that in law enforcement against narcotics crimes, according to the narcotics law, criminal sanctions will be imposed, fines, life imprisonment and other sanctions. The system of association and the level of understanding and awareness of the substance of narcotics.